Abstract: The importance of this research come from the aspect of international criminal court and their judicial specialization in justice the state's affiliates about the limited crimes enter within their specialist . at the same time these crimes menti (مجلة المنصور, 2022)
The Randomness is one of the basic criterions to measure stream cipher Efficiency. The stream cipher generator depends basically on Linear FeedBack Shift Register which is considered as one of the basic units of Stream Cipher Systems. In this paper, the frequency postulate of Randomness criteria is calculated theoretically for non-linear stream cipher systems before it be implemented or constructed (software or hardware), this procedure save time and costs. Two non-linear stream cipher generators are chosen to apply the theoretical studies; these key generators are the Complement Product and Shrinking Generators. The theoretical proofs of frequency estimation for the two key generators are introduced.